SPATIO-TEMPORAL PATTERN AND FACTORS ASSOCIATED WITH TUBERCULOSIS MORTALITY IN A NORTHEASTERN STATE - BRAZIL - George Jó Bezerra Sousa; Bruno Victor Barros Cabral; Antonio Marcílio Silveira Silva; Monalisa Ribeiro Alves; Thatiana Araujo Maranhão; Maria Lúcia Duarte Pereira (Cogitare Enfermagem, 2022)
Objective: to identify the spatio-temporal pattern of tuberculosis mortality and its related factors.